2012
DOI: 10.1002/jclp.21912
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Psychological Telehealth: Current and Future Clinical Psychologists’ Opinions of Internet‐Based Interventions

Abstract: Increasing exposure to telehealth through education as well as continued research on efficacy for specific diagnoses may help psychologists to more effectively determine whether telehealth is the "best fit" for both clinician and client.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
120
5
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 60 publications
18
120
5
7
Order By: Relevance
“…In the case of psychologists, over 70% of them were interested in learning more about web technologies in their practice (Perle et al, 2013). This finding was fairly consistent with our MFT sample, where 85.3% (n ¼ 153) indicated they were somewhat interested in learning about web practices.…”
Section: Implications For Trainingsupporting
confidence: 90%
See 1 more Smart Citation
“…In the case of psychologists, over 70% of them were interested in learning more about web technologies in their practice (Perle et al, 2013). This finding was fairly consistent with our MFT sample, where 85.3% (n ¼ 153) indicated they were somewhat interested in learning about web practices.…”
Section: Implications For Trainingsupporting
confidence: 90%
“…The findings presented here represent a subset of the complete survey tool and focus on counselor perceptions of the potential ethical issues when participating in online therapy practices, and the extent to which guidelines from other organizations, and opportunities for further training would be desired. Because the findings in the Perle et al (2013) study contradicted the findings of the Mora, Nevid, and Chaplin (2008) with regard to differences in student versus professional perceptions and practices, data regarding the importance of using other ethical codes to make decisions were analyzed through a t-test to determine whether there was a difference between students and professionals. The analysis with regard to the openended items involved noting common phrases within the answer to each prompt following an open and thematic coding process (Merriam, 2002).…”
Section: Instrumentmentioning
confidence: 98%
“…Providers and their choices about treatment modalities used may also be impacted by their own attitudes toward and perceptions of TMH. 23 For example, in a study that surveyed mental health professionals, Perle et al 24 found lower general levels of acceptance toward technology-mediated interventions compared with face-to-face services, which also varied widely by type of psychiatric diagnosis. Some researchers have begun to address these issues more directly, with some emerging support for comparable patient ratings of working alliance for inperson and e-therapy (text-based) treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Typically, sociodemographic characteristics such as younger age, higher educational level, Internet access, and technical experience have been associated with acceptance of eHealth interventions in several studies [2,27,49,50]. Further potential barriers to acceptance include Internet anxiety [40,51], low Internet orientation in health problems [27], insufficient knowledge of eHealth interventions [27,52], rural residence [53], or reservations regarding data security or impersonal interaction [54,55]. However, barriers or facilitators to eHealth adoption in inpatient routine care have not been studied sufficiently yet.…”
Section: Introductionmentioning
confidence: 99%